Characterisation of platinum electrodeposits on a titanium micromesh stack in a rectangular channel flow cell. (1st September 2017) - Arenas, Luis F.; Ponce de León, Carlos; Boardman, Richard P.; Walsh, Frank C.
Graphical abstract: Abstract: Platinised titanium mesh is a common electrode material in industrial electrolytic cells and Ce-based redox flow batteries. In this work, the electrodeposition of platinum on a stack of titanium micromeshes is performed from a flowing alkaline solution in a rectangular channel, divided flow cell. The morphology and distribution of the resulting platinum deposits are studied by SEM, EDS mapping and X-ray computed tomography. The active surface area of the electrode was assessed from the charge transfer current for the reduction of Ce(IV) ions and compared to that of planar and expanded metal mesh electrodes. The surface area was estimated by hydrogen electrosorption relative to that at a planar Pt/Ti electrode. As expected from the potential drop within the electrode channel, the individual micromesh near the cell separator showed a higher platinum content. Pt/Ti micromesh offers an extended surface area and enhanced mass transport compared to planar electrodes and conventional expanded metal mesh anodes. The applications for these and alternative electrode structures are discussed.